CHRONIC PELVIC PAIN SYNDROME WITH CHRONIC SALPINGOOPHORITIS – A MODERN VIEW ON PATHOGENESIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article presents a retrospective analysis oitis, in 243 of them this condition was complicated by chronic pelvic pain syndrome (ChPPS).